2004
DOI: 10.1200/jco.2004.12.185
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Study of the Proteasome Inhibitor Bortezomib in Pediatric Patients With Refractory Solid Tumors: A Children's Oncology Group Study (ADVL0015)

Abstract: Bortezomib is well tolerated in children with recurrent or refractory solid tumors. The recommended phase II dose of bortezomib for children with solid tumors is 1.2 mg/m2/dose, administered as an intravenous bolus twice weekly for 2 weeks followed by a 1-week break.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
66
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(71 citation statements)
references
References 12 publications
4
66
0
1
Order By: Relevance
“…The role of bortezomib in the treatment of various pediatric solid malignancies has also been investigated by Blaney et al [87] . Thrombocytopenia was the only dose-limiting toxicity but no objective responses were found.…”
Section: Phase I Clinical Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of bortezomib in the treatment of various pediatric solid malignancies has also been investigated by Blaney et al [87] . Thrombocytopenia was the only dose-limiting toxicity but no objective responses were found.…”
Section: Phase I Clinical Trialsmentioning
confidence: 99%
“…Thrombocytopenia was the dose-limiting toxicity and the maximum tolerated dose regimen was determined to be 1.0 mg/m 2 for bortezomib and 1000 mg/m 2 for gemcitabine. (2004) [87] Refractory solid tumors (pediatrics) [99] Advanced NSCLC In the study of Albanell et al [84] , bortezomib was administered with docetaxel to anthracycline-treated patients who had advanced breast carcinoma. The maximum tolerated dose had not been reached; however, dose-limiting toxicities of febrile neutropenia and neuropathy occurred in 14% of patients.…”
Section: Phase I Clinical Trialsmentioning
confidence: 99%
“…In this setting, bortezomib (Velcade) was demonstrated to be effective in the treatment of multiple myeloma and non-Hodgkin's lymphoma, when taken alone or in combination with traditional anticancer drugs [3][4][5][6][7]. Similarly, preliminary studies indicated that proteasome inhibitors induce clinical responses in patients with acute leukemia, prostate cancer, renal cell carcinoma, neuroendocrine tumors, and in children solid tumors [8][9][10][11][12]. How proteasome inhibition translates into a potent cytotoxic effect in tumor cells is not fully understood, even though inhibition of NF-jB and deregulated expression of p53, caspases, Bcl-2 family members, CDC25 family proteins and cyclins were all proposed to be relevant in this context [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…22 This has been exploited in the therapy of malignancies in which tumor cells have been shown to have preferential sensitivity to the proapoptotic effects of proteasome inhibition. [23][24][25][26][27] Studies in murine tumor models 28,29 and small clinical studies 30,31 have shown activity against a spectrum of malignancies. In addition, bortezomib has recently been approved for the treatment of patients with relapsed multiple myeloma in whom response rates of 40% have been observed after the failure of high-dose therapy followed by stem cell transplantation.…”
Section: Introductionmentioning
confidence: 99%